Effective silicon production from SiCl4 source using hydrogen radicals generated and transported at atmospheric pressure. Issue 1 (31st January 2020) - Okamoto, Yuji; Sumiya, Masatomo; Nakamura, Yuya; Suzuki, Yoshikazu
ABSTRACT: In the Siemens method, high-purity Si is produced by reducing SiHCl3 source gas with H2 ambient under atmospheric pressure. Since the pyrolysis of SiHCl3, which produces SiCl4 as a byproduct, occurs dominantly in the practical Siemens process, the Si yield is low ( 30%). In the present study, we generated hydrogen radicals (H-radicals) at pressures greater than 1 atm using tungsten filaments and transported the H-radicals into a reactor. On the basis of the absorbance at 600 nm of WO3 -glass exposed to H-radicals in the reactor, we observed that H-radicals with a density of 1.1 × 10 12 cm −3 were transported approximately 30 cm under 1 atm. When SiCl4 was supplied as a source into the reactor containing H-radicals and allowed to react at 850°C or 900°C, Si was produced more efficiently than in reactions conducted under H2 ambient. Because the H-radicals can effectively reduce SiCl4, which is a byproduct in the Siemens method, their use is expected to increase the Si yield for this method. Graphical abstract: uf0001